Symbolism, solitude and modernity: science and scientists in porfirian Mexico Simbolismo, solidão e modernidade: ciência e cientistas no México porfiriano - Natalia Priego (História, Ciências, Saúde: Manguinhos)
The quest of Mexico for a distinctive national identity throughout the 19th century reached a climax during the period known as the Porfiriato, one of the principal features of which was the deep desire of Porfirio Díaz and his circle to turn Mexico into a 'modern' country perhaps without a clear definition of the meaning of this concept. The debate about national identity had addressed such issues as the rejection of indigenous cultures, blind passion for French culture, and how to go about criating a modern nation by means of industrialization and scientific modernization. The concept of nation in Mexico is definitively linked with the search for a national 'I', and with the struggle to overcome the solitude identified by Octavio Paz. Paradoxically, this very quest forms a part of this identity, and it seems to remain inconclusive. Ao longo do século XIX, a tentativa de construir uma identidade nacional para o México atingiu seu ápice no período conhecido como Porfiriato, que teve como uma das principais características o desejo profundo de Porfírio Díaz e seu grupo de transformar o país em uma nação moderna, sem ter uma definição clara do significado desse conceito. O debate sobre identidade nacional tinha enfrentado questões como a negação de culturas indígenas; a paixão cega pela cultura francesa e todo um savoir faire diante do esforço de se criar uma nação moderna através da industrialização e da modernização científica. O conceito de nação, no México, é estreitamente vinculado à busca pelo 'eu' nacional e à luta para ultrapassar a solidão descrita por Octávio Paz. Paradoxalmente, esta busca forma uma parte dessa identidade, e parece inconclusa.